Enhancement of mechanical properties of the AA5754 aluminum alloy with a severe plastic deformation - Izairi, Neset (Materiali in tehnologije, 2014)
Mechanical properties of materials with ultrafine grain (UFG) size have attracted considerable scientific attention and technological interest during the last few years. It was well established that the grain size of metallic alloys may be substantially refined with a severe plastic deformation (SPD). The present work focuses on equal-channel angular pressing (ECAP) as the most used method of SPD for grain refinement inducing a significant enhancement to the mechanical and functional properties of the commercial AA5754. ECAP with up to 6 passes resulted in a substantial grain-size reduction from 70 %m of an as-received sample to 5 %m. The aforementioned reduction of the grain size increased the microhardness by a factor of 4. These results were compared to those of AA3004.
Keywords: severe plastic deformation; velika plastična deformacija; ultradrobna zrna; equal-channel angular pressing; mechanical properties; mehanske lastnosti; microhardness; mikrotrdota; natezni preizkus; tensile test